A novel deleterious c.2656G>T MSH2 germline mutation in a Pakistani family with a phenotypic overlap of hereditary breast and ovarian cancer and Lynch syndrome. Issue 1 (December 2016) - Rashid, Muhammad; Naeemi, Humaira; Muhammad, Noor; Loya, Asif; Yusuf, Muhammed; Lubiński, Jan; Jakubowska, Anna; Hamann, Ute
Abstract Background Hereditary breast and ovarian cancer syndrome (HBOC) and Lynch syndrome (LS) account for a significant proportion of inherited gynecologic malignancies, mainly caused by pathogenic germline mutations in theBRCA1 andBRCA2 genes or in mismatch repair (MMR ) genes, such asMLH1 andMSH2 . Women harboring deleterious mutations in these genes have increased life-time risks of developing a number of malignancies including ovarian cancer. Since there is a phenotypic overlap of HBOC and LS, timely identification of individuals at-risk of a particular syndrome is crucial in order to optimize cancer risk management. Case presentation We report a novel pathogenicMSH2 mutation, c.2656G > T, which was identified in a 67-year-old female patient with breast cancer, who had previously tested negative for a deleterious mutation in the breast cancer susceptibility genesBRCA1, BRCA2, CHEK2 orRAD51C . The patient reported a personal history of endometrial cancer diagnosed at age 48, and a strong family history of breast and ovarian cancer, as well as several other malignancies within the spectrum of LS. The novel mutation was also found in the index patient's daughter and a niece, who were diagnosed with endometrial and ovarian cancer, respectively. Breast and endometrial tumors from c.2656G > T mutation carriers showed loss of MSH2 and MSH6 protein expression. The mutation was absent in the control population. Conclusions Our finding suggests that testing forMMR genes may be of benefit toBRCA1/2 negative families with overlapping HBOC and LS phenotype in Pakistan. It is clinically significant to identify individuals harboring mutations in genes linked with a particular syndrome so that they can benefit from targeted life-saving cancer surveillance and preventive strategies.